The Mediation Roles of Coping Modalities on the Relationship Between Stress and Quality of Life Among Jordanian Nurses - Wafa’a Ta’an; Yasin Yasin; Mohammed M. Al-Hammouri; Majd Aljabali; Diana Jaradat; Mohammad Suliman; Mohammed Albashtawy; Islam Oweidat; Yazid Al-Hamarneh (The Scientific World Journal)
Nurses are at the frontline, dealing with people’s most immense healthcare needs in stressful and demanding work environments. Consequently, it is essential to thoroughly examine how various coping mechanisms might affect the relationship between stress and quality of life (QOL). This study aimed to examine the mediation effect of both problem-focused coping (PFC) and emotion-focused coping (EFC) mechanisms on mitigating the effect of stress on the QOL among Jordanian nurses. A multisite cross-sectional descriptive correlational design was used in this study. An online survey was completed by 203 nurses using a convenience sampling technique between October 2023 and January 2024. The study included nurses working in different Jordanian healthcare sectors including governmental, private, and university-affiliated hospitals. Several measures were used to collect data, including questionnaires on sociodemographics, QOL, coping, and stress. Two models were hypothesized for this study. The two models were analyzed using Andrew Hayes Process Macro Model 4 for testing the mediation effects. Additionally, descriptive and correlational analyses were run prior to the main analysis. The results showed that coping significantly mediated the relationship between stress and QOL with variations between PFC and EFC. In conclusion, psychological distress symptoms were common among Jordanian nurses; psychological distress, coping, and QOL are correlating variables. Nurses’ stress levels and coping modalities can predict QOL with a superior effect of PFC compared with EFC. Strategies should be put in place to improve effective coping to improve nurses’ QOL. The results of this study have important implications for nursing education, practice, future research, and policy.